Pemanfaatan Kecerdasan Buatan dalam Pendidikan di Indonesia: Potensi dan Tantangan - Oktavia, Devi Haryanti; Suseno, Giri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of Smart Technology (AI) in the education sector in Indonesia, considering its opportunities and obstacles, is evaluated in this article. This study aims to discuss the potential and challenges of using AI in education in Indonesia. Literature studies are used, with various related studies having been published. AI offers great potential to support more individualized and responsive education, including automated evaluation and increased student participation. To face the risks and prospects of the digital era, Indonesian students are required to understand AI. Although the adoption of AI raises various barriers, including privacy, moral, and digital divide, this article emphasizes the need for a strong legal and ethical framework to control the use of AI in Indonesia. The training of teachers to utilize AI efficiently in their teaching practices was also highlighted. The huge potential offered by AI for education in Indonesia requires a careful and balanced approach to maximize benefits and minimize risks as a general assessment